PENGARUH LATIHAN MENGGUNAKAN PAPAN TOLAKMIRING TERHADAP KETEPATAN JUMP SERVICE PADA BOLA VOLI - Prasetyo, Yona Bayu; Saichudin, Saichudin; Andiana, Olivia (Jurnal Sport Science, 2017)
Abstract :Servis is the first blow in volleyball and also as first attack on avolleybal. One technique which is recently used by jump service. to increase the ability to jump right on target service to be performed by using slanting reject board. This research procedure using pre-ekspermental research, where there is only one group of subjects, namely the experimental group, the research was conducted through several stages, including: 1) the initial step, 2) conduct step, 3) manage data step. The instrument is a test of skill used for servicing of AAHPER. The subjects were students in extracurricular volleyball MAN Ngawi of 20 people. From the results of paired t-test using a technique paired sample test values obtained Sig. (2-tailed) with a level of p = 0.000 <Î± = 0.05, the results of the exercise using board reject oblique a significant influence on the accuracy of punches jump service to students extracurricular volleyball MAN Ngawi. Based on these results Its could be concluded that the practice of using board reject oblique has a significant effect on the accuracy of punches jump service on student extracurricular volleyball MAN Ngawi.Keywords :experiment, exercises using reject board oblique, accuracy jump